The Outcome of Different Surgical Conditions in Neonates at A Tertiary Care Hospital: A Cross-Sectional Study - Ishrat Mahtam, Sirajuddin Soomro, Sumaira (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the outcome of different surgical conditions in neonates at a tertiary care hospital Study design: A cross-sectional study Place and Duration: Department of Pediatric Surgery Chandka Medical College Children’s hospital Larkana from Nov 2020 to Nov 2021 Methodology: All the neonates with surgical conditions were admitted through emergency and OPD. The variables were age, gender, diagnosis, surgery performed, postoperative course and complications if any. Patients soon after birth to 28 days of age with neonatal surgical conditions were enrolled in the study. The diagnosis was established either with pre-operative, intra-operative or post-operatively with relevant clinical, radiological, biochemical and histopathological findings described in standard textbooks of paediatric and neonatal surgery Results: A total of 208 patients were managed. The age range was 1 hour to 28 days. Male was 159 (76.4%) and 49 (23.6%) were female. The commonest conditions presented were anorectal malformations followed by necrotizing enterocolitis. Other conditions include Hirschsprung’s Disease, Omphalocele, Gastroschisis, Duodenal and Jejuno ileal Atresia, Myelomeningocele, Infantile Hypertrophic Pyloric Stenosis, Obstructed Inguinal Hernias, sacrococcygeal teratoma and skin and soft tissue infections. Frequently performed operation was the creation of stoma (Colostomy/Ileostomy). 180 (86.53%) neonates were discharged and 24 (11.53%) neonates expired while only 4 (1.92%) neonates were referred to other centers. Conclusion: Neonatal surgical conditions carry high mortality and morbidity even at centers with all facilities available. Our results at the resource-limited centre are comparable to the centres having state of art facilities. Keywords: Neonatal surgery, Anorectal Malformations, Abdominal wall defects, Necrotizing Enterocolitis (NEC)